Melatonin, consciousness, and traumatic stress - Bob, Petr; Fedor-Freybergh, Peter (Journal of Pineal Research, 2008)
Abstract: Descartes intuitively anticipated the so-called ‘binding problem’ of consciousness and thought that the pineal gland enables spatio-temporal integration in cognitive processing. Recent findings indicate that a major role in the process of temporal integration and binding involve neurons in suprachiasmatic nuclei, specifically targeting the pineal gland and other structures, and control the neuroendocrine rhythms. Melatonin is an endocrine output signal of the clock and provides circadian information as an endogenous synchronizer which stabilizes and reinforces circadian rhythms. This integrative process occurs at the different levels of the circadian network via gene expression in some brain regions and peripheral structures that enables integration of circadian, hormonal, and metabolic information and creating temporal order of bodily and mental experience. This specific temporal order is reflected in associative sequentiality that is necessary for cognition, behavior and all processes of memory consolidation that must preserve all information in the temporal causal order and synchrony. In this context, recent findings suggest that melatonin could be a potential regulator in the processes that contribute to memory formation, long-term potentiation, and synaptic plasticity in the hippocampus and other brain regions. There is evidence that stress disrupts normal activity and memory consolidation in the hippocampus and prefrontal cortex, and this process leads to memories that are stored without a contextual or spatiotemporal frame. These findings emphasize a specific role of melatonin in mechanisms of consciousness, memory and stress and are also consistent with reported studies that indicate melatonin alterations under stressful conditions and in mental disorders.
Keywords: consciousness; dissociation; melatonin; memory; pineal gland; stress